Multisystem inflammatory syndrome in children associated with SARS-CoV-2 infection: diagnosis and differential diagnosis - O.P. Volosovets; S.P. Kryvopustov (Zdorovʹe Rebenka, 2025)
Multisystem inflammatory syndrome in children (MIS-C) is a new pediatric hyperinflammatory disease. Its prevalence is 0.69 cases per 1,000 SARS-CoV-2 infections, and the fatality rate is 1–2 %. There is an evolution in the criteria for its diagnosis. Today, in the updated criteria, the following signs are crucial in the absence of an alternative diagnosis: fever ≥ 38.0 °C; clinical severity requiring hospitalization or leading to death; signs of systemic inflammation (C-reactive protein ≥ 30 mg/l); and new manifestations of two of the following signs: heart damage; skin and mucosal lesions; shock; damage to the gastrointestinal tract; hematological changes, as well as laboratory or epidemiological confirmation of COVID-19 sixty days before hospitalization. The current 2023 MIS-C definition differs from the previous one in that the duration of fever is absent, an inflammatory threshold (C-reactive protein ≥ 30 mg/L) is included, the number of organ systems involved is reduced, shock is considered as a separate category, and Kawasaki disease is defined as an alternative diagnosis. Clinical manifestations of MIS-C can mimic other conditions, for example, sepsis, toxic shock syndrome, Kawasaki disease, some viral, autoimmune diseases, etc. In MIS-C, in addition to fever, gastrointestinal symptoms, skin and mucosal lesions, and myocarditis are more common, and NT-pro-BNP levels may be a prognostic indicator. Early identification and treatment of MIS-C with intravenous immunoglobulins, corticosteroids, and biologics are crucial, which makes competent differential diagnosis extremely important. In contrast to Kawasaki disease, MIS-C is characterized by higher levels of D-dimer, troponin, NT-proBNP, thrombocytopenia and elevated ferritin; pleural effusion, renal involvement, and gastrointestinal symptoms are more common, but coronary artery anomalies are less significant. In the differential diagnosis with sepsis, positive blood cultures, absence of contact with COVID-19 patients, leukocytosis, procalcitonin, and the MISSEP score should be considered. In the differential diagnosis with toxic shock syndrome, it should be taken into account that the infectious process is mainly associated with strains of Staphylococcus aureus or Streptococcus pyogenes that produce toxins, the onset of symptoms is more sudden, and they progress faster than in MIS-C.